Development of a Laser Frequency Stabilization and an Optical Transmission System for the Francium Electric Dipole Moment Search. Issue 1 (1st April 2022) - Nakamura, K; Nagase, S; Nakashita, T; Hayamizu, T; Aoki, T; Nagahama, H; Ozawa, N; Sato, M; Yamane, K; Fukase, M; Uehara, D; Takamine, A; et al.
Abstract: We developed a laser frequency stabilization and an optical fiber transmission system for the the francium electric dipole moment search. The absolute accuracy of a laser frequency stabilization scheme using a state-of-the-art commercial wavelength meter was 0.48 MHz at ±2 nm and -1.33 MHz at ±200 nm from calibration wavelength, respectively, and the frequency instability is below 10 -9 with a standard deviation of 0.56 MHz over 60 hours. We also demonstrated that a 400 m long fiber laid between laboratories can transmit 30 mW of trapping laser light, which is sufficient for a magneto-optical trapping of francium. The polarization crosstalk in the fiber was stable at -25 dB over 12 hours of measurement.